Policy-Driven Inter-Organisational Networks For Competency Development: A Study Of Malaysia's MSC Flagship Networks - Omar, Aliza Akma (2008)
This study addresses whether organisations can be driven to develop competencies when participating in policy-driven inter-organisational networks - the networks being the flagship projects of Malaysia's Multimedia Super Corridor (MSC) initiative.